Human papillomavirus, radiation dose and survival of patients with anal cancer. (2nd December 2019) - Kabarriti, Rafi; Brodin, N. Patrik; Ohri, Nitin; Narang, Rahul; Huang, Renee; Chuy, Jennifer W.; Rajdev, Lakshmi N.; Kalnicki, Shalom; Guha, Chandan; Garg, Madhur K.
Abstract: Purpose: To determine if anal cancer patients with HPV positive disease have different overall survival (OS) compared to those with HPV negative disease, and to elucidate differences in the association between radiation dose and OS. Patients and methods: We utilized the National Cancer Database (NCDB) registry to identify a cohort of non-metastatic anal cancer patients treated with curative intent between 2008 and 2014. Propensity score matching was used to account for potential selection bias between patients with HPV positive and negative disease. Multivariable Cox regression was used to determine the association between HPV status and OS. Kaplan–Meier methods were used to compare actuarial survival estimates. Results: We identified 5927 patients with tumor HPV status for this analysis, 3523 (59.4%) had HPV positive disease and 2404 (40.6%) had HPV negative disease. Propensity-matched analysis demonstrated that patients with HPV positive locally advanced (T3–4 or node positive) anal cancer had better OS (HR = 0.81 (95%CI: 0.68–0.96), p =.018). For patients with early stage disease (T1–2 and node negative) there was no difference in OS (HR = 1.11 (95%CI: 0.86–1.43), p =.43). In the unmatched cohort, we found a significant improvement in OS with increasing radiation dose only for patients with locally advanced, HPV negative disease ( p <.001). In those patients, significant improvement in OS compared to the group receiving 30–45 Gy was seen for increasing doses up to 55–60 Gy, but not beyond 60 Gy. Conclusion: We found HPV to be a significant prognostic marker in anal tumors, especially for locally advanced disease. We further found that higher radiation dose up to 55–60 Gy was associated with better OS, but only for patients with locally advanced, HPV negative disease.